Oral Swab-Based DNA Extraction Of Cynopterus Brachyotis: An Initial Step For Species Confirmation - Nabila Aulia Rhamadaningtyas; Elly Lestari Rustiati; Priyambodo Priyambodo; Eko Agus Srihanto; Enny Saswiyanti; Dian Neli Pratiwi; Alvin Wiwiet Susanto (Ann Publisher, 2026)
Background. Identifying bat species based on morphological characteristics often faces challenges due to character overlap among species, especially within cryptic species groups. Cynopterus brachyotis is one of the fruit bats with high genetic diversity but relatively uniform morphology. Aims. Therefore, a molecular approach is needed to support accurate species confirmation. Under the HETI Research Grant of Innovation and Collaboration Batch 3- II Year 2025, this study aims to obtain genomic DNA from C. brachyotis bats caught at the Lampung Disease Investigation Center as the initial step of molecular species confirmation. Methods. Samples were obtained by taking oral swabs on bat individuals caught using mist nets. DNA extraction is performed using silica membrane-based methods with commercial kits. Quantitative evaluation of DNA was performed using a Qubit Fluorometer, while qualitative evaluation was performed by agarose gel electrophoresis. Conclusion. The results showed that the DNA concentration was in the low range (0.1–0.7 ng/μL), with a DNA band appearing very thin on electrophoresis. Implementation. Nevertheless, the quantification results confirm that DNA was successfully extracted and remains suitable for advanced molecular analysis, with optimization at the DNA amplification stage.